The case of Ethiopia’s enjera markets: Synopsis: Food processing, transformation and job creation - Minten, Bart; Assefa, Thomas; Abebe, Girum; Tamru, Seneshaw; Engida, Ermias (International Food Policy Research Institute, 2017)
Given the importance of agriculture in developing economies, food processing industries often dominate employment and value addition in the industrial sector in these settings. For example, it is estimated that the food processing industry in Ethiopia employs one million people, around 2 percent of the economically active population. However, the way in which Ethiopia’s food processing industry is changing and how it functions is little understood. We study the markets in urban Ethiopia for commercial ready-to-eat enjera, the traditional staple pancake of the country. We find that these commercial enjera markets are rapidly growing, employing more than 100,000 people in urban Ethiopia, many of whom are women. Moreover, enjera is now being prepared by mixing flour from locally produced teff with that of imported rice, thus absorbing an important part of the rapidly growing rice imports (almost 200 million USD in 2015) to the country and leading to higher profits for those enterprises en